PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 4A DI SEKOLAH DASAR KRISTEN PENABUR KOTA MODERN - Soegeng Wahyoedi; Letelay, Santi Erlanda Magdalena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aims to investigate the effectiveness of Project-Based Learning (PBL) in enhancing students’ learning motivation in Class 4A at SDK PENABUR Kota Modern. The study was conducted over two cycles, using the Kemmis and McTaggart model, which includes planning, action, observation, and reflection. Data were collected through questionnaires, observations, interviews, and documentation. Quantitative analysis involved descriptive statistics, Spearman correlation, Wilcoxon, and Mann-Whitney tests, while qualitative analysis included thematic analysis from interviews and observations. The results showed a significant increase in students’ learning motivation after the implementation of PBL, especially in extrinsic motivation and technology engagement, though intrinsic motivation remained relatively stable. Students responded positively to collaborative learning and the use of digital tools such as Google, YouTube, and Canva. However, challenges such as group conflicts and project duration were identified. The findings suggest that PBL, when effectively managed and supported by relevant technology, can serve as an impactful approach to boost students' motivation and foster 21st-century skills in primary education.